Examination the effects of Stefan blowing on chemical reactive flow of hybrid nanofluid over an infinite disk with Cattaneo-Christove heat flux model - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; Rezapour, Shahram; İnç, Mustafa (Taylor & Francis Ltd, 2025)
This research proposal investigates the impact of inclined magnetohydrodynamics (MHD) and Stefan blowing on an axisymmetric chemical convective flow of HNF (hybrid nanofluid) across an infinite disc. Analysis is done on Joule heating's effects and non-uniform heat generation. The Cattaneo-Christov heat flow model is employed for studying thermal transfer properties. The addition of the time for thermal relaxation to the original Fourier's law makes this new heat flux model more comprehensive. This model's goal is to evaluate the effectiveness of the Hamilton-Crosser and Xue hybrid nanofluid models. The (RKF-45th) algorithm is employed to numerically solve this issue. The effects of different physical and flow factors on temperature, concentration, and flow behavior, as well as the rate of heat/mass phenomenon, are scrutinized using tables and graphs. The findings show that while fluid flow increases as the Stefan blowing factor rises, temperature, heat, and mass transmission rate decrease.
Keywords: Stefan blowing impacts; chemical reaction; Cattaneo-Christove heat flux model; Hybrid nanofluid; Hamilton-Crosser and Xue models